BACE INHIBITORS - HEMBRE ERIK JAMES; WATSON BRIAN MORGAN; GREEN STEVEN JAMES; WINNEROSKI JR. LEONARD LARRY; SHI YUAN; MERGOTT DUSTIN JAMES (2016)
본 발명은 하기 화학식 III의 화합물, 또는 제약상 허용되는 염을 제공한다. <화학식 III>상기 식에서, A는이고; Z, R, R, R, 및 R는 본원에 정의된 바와 같다. The present invention provides a compound of Formula III: Formula III wherein A is: and Z, R1, R2, R3, and R4 are as defined herein, or a pharmaceutically acceptable salt thereof, which is useful for treating Alzheimer's disease.